Collective Behavior and the Generality of Integrated Theory: A National Study of Gang Fighting. Issue 8 (3rd August 2018) - Collins, Angela M; Menard, Scott; Pyrooz, David
ABSTRACT: This paper uses integrated theory to explain gang fighting. Integrated theory combines elements of social control, social learning, and strain theories. We focus on gang fighting to assess the generality of integrated theory because it constitutes serious violent collective behavior which is linked to other problem behaviors. Few explanations for such behavior are offered. We examine the relationship between integrated theory and gang fighting using multi-level modeling and data from the first five waves of the National Youth Survey Family Study for the period 1976–1980. Support for direct effects of some components of integrated theory was found, including normlessness, delinquent peer-group bonding, and grades in school.